REVIEWS - Griffel, Frank (Journal of Semitic studies, 2003)
Al-Ghazālī and the Ismailis. A Debate on Reason and Authority in Medieval Islam (Ismaili Heriate Series, 5) Farouk Mitha , I.B. Taurus in association with the Institute of Ismaili Studies, London 2001. Pp. 128. Price: £25.00 hardback/£12.95 paperback. ISBN: 1-86064-792-8 hbk/1-86064-819-3 pbk.